Associated factors with negative health perception and quality of life of Brazilian older adults - Barbosa, Felipe Douglas Silva (2020)
The purpose of this study was to analyze the factors associated with negative Health Perception and Quality of Life (QoL) of older adults. This was a cross-sectional study composed of 224 older adults with a median age of 70.58±6.43 years old. A questionnaire was designed to incorporate ABEP (socioeconomic questionnaire), WHOQOL-BREF, IPAQ, and Senior Fitness Test (SFT). Binary logistic regression with p>0.05, organized in univariate and multivariate models in SPSS version 22. Variables upper extremities poor flexibility OR = 2.43 (1.37 – 4.31) and lower extremities poor flexibility OR = 2.69 (1.54 – 4.69) were significantly associated with negative health perception. Being not financial responsible OR= 0.33 (0.12 – 0.85) presented lower odds of negative QoL perception. The variable Lower extremities poor flexibility univariate OR= 2.52 (1.45 – 4.39) and multivariate model OR= 2.42 (1.38 – 4.24) showed almost three times higher probabilities of negative QoL perception.